Electric‐Field‐Induced Alignment of Block Copolymer/Nanoparticle Blends. Issue 19 (13th March 2013) - Liedel, Clemens; Schindler, Kerstin A.; Pavan, Mariela J.; Lewin, Christian; Pester, Christian W.; Ruppel, Markus; Urban, Volker S.; Shenhar, Roy; Böker, Alexander
Abstract External electric fields readily align birefringent block‐copolymer mesophases. In this study the effect of gold nanoparticles on the electric‐field‐induced alignment of a lamellae‐forming polystyrene‐block‐poly(2‐vinylpyridine) copolymer is assessed. Nanoparticles are homogeneously dispersed in the styrenic phase and promote the quantitative alignment of lamellar domains by substantially lowering the critical field strength above which alignment proceeds. The results suggest that the electric‐field‐assisted alignment of nanostructured block copolymer/nanoparticle composites may offer a simple way to greatly mitigate structural and orientational defects of such films under benign experimental conditions.